2013
DOI: 10.3109/00952990.2013.848213
|View full text |Cite
|
Sign up to set email alerts
|

Altered resting-state connectivity in adolescent cannabis users

Abstract: The reduced interhemispheric RSFC in adolescent cannabis users complements previous reports of white matter deficits associated with cannabis use. The evidence of elevated connectivity within the right hemisphere may reflect a compensatory mechanism. Combined, the results suggest that altered intrinsic connectivity may be characteristic of adolescent cannabis dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
54
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 56 publications
9
54
1
1
Order By: Relevance
“…An illustrative example comes the cannabis literature. Initial functional connectomics studies of chronic cannabis use in adolescence have already furnished a number of findings (Behan et al, 2014; Orr et al, 2013), which are particularly intriguing given recent secular trends in the legal status of cannabis in many western societies. However, the reliance of these efforts on retrospective designs precludes determinations of whether abnormalities in brain structure and function were pre-existing deficits or sequelae of early substance use (for review see: Jacobus and Tapert, 2014).…”
Section: Section 1: Developmental Miswiring: Emerging Modelsmentioning
confidence: 99%
“…An illustrative example comes the cannabis literature. Initial functional connectomics studies of chronic cannabis use in adolescence have already furnished a number of findings (Behan et al, 2014; Orr et al, 2013), which are particularly intriguing given recent secular trends in the legal status of cannabis in many western societies. However, the reliance of these efforts on retrospective designs precludes determinations of whether abnormalities in brain structure and function were pre-existing deficits or sequelae of early substance use (for review see: Jacobus and Tapert, 2014).…”
Section: Section 1: Developmental Miswiring: Emerging Modelsmentioning
confidence: 99%
“…Increased parietal-cerebellar, right hemispheric, and PFC (Behan et al, 2013; Orr et al, 2013) and decreased frontal-cerebellar interhemispheric and temporal cortex (Houck et al, 2013; Orr et al, 2013) resting state connectivity has been reported in adolescent cannabis users. Studies have also found increased functional connectivity between PFC-occipital (Harding et al, 2012), and parietal-cerebellar (Behan et al, 2013) brain regions in adolescent cannabis users while engaging in cognitive tasks.…”
Section: Impacts Of Regular Cannabis Use On Neurocognition In Teenmentioning
confidence: 99%
“…Therefore, cannabis exposure may influence reward circuit function by altering the connectivity of key regions. Congruently, several studies have reported altered connectivity in association with cannabis use, including aberrant resting-state functional connectivity (rsFC) of the default mode, insula, and lateral visual networks among cannabis users (17, 18), reduced interhemispheric rsFC among cannabis dependent adolescents (19), and heightened rsFC of the medial frontal gyrus in association with cannabis use among high risk youth (20). Furthermore, increased functional connectivity between the PFC and occipitoparietal cortex has been reported in association with increased cognitive control demands among heavy cannabis users relative to controls (21), and cannabis dependent individuals display heightened functional connectivity between the PFC and basal ganglia during successful inhibition, relative to non-dependent cannabis users (22).…”
Section: Introductionmentioning
confidence: 99%